Inhibition of Amyloid-Beta Production, Associated Neuroinflammation, and Histone Deacetylase 2-Mediated Epigenetic Modifications Prevent Neuropathology in Alzheimer’s Disease in vitro Model - Atluri, Venkata Subba Rao; Tiwari, Sneham; Rodriguez, Melisa; Kaushik, Ajeet; Yndart, Adriana; Kolishetti, Nagesh; Yatham, Mohan; Nair, Madhavan (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a growing global threat to healthcare in the aging population. In the US alone, it is estimated that 1 in 9 persons over the age of 65 is living with AD. The pathology is marked by the accumulation of amyloid-beta (Aβ) deposition in the brain, which is further enhanced by the neuroinflammatory process. Nucleotide-binding oligomerization domain-like receptor (NLRP3) and nuclear factor-kB (NF-kB) are the major neuroinflammatory pathways that intensify AD pathogenesis. Histone deacetylase 2 (HDAC2) mediated epigenetic mechanisms play a major role in the genesis and neuropathology of AD. Therefore, therapeutic drugs, which can target Aβ production, NLRP3 activation, and HDAC2 levels, may play a major role in reducing Aβ levels and the prevention of associated neuropathology of AD. In this study, we demonstrate that Withaferin A (WA), an extract from Withania somnifera plant, significantly inhibits the Aβ production and NF-kB associated neuroinflammatory molecules gene expression. Furthermore, we demonstrate that cytokine release inhibitory drug 3 (CRID3), an inhibitor of NLRP3 significantly prevents inflammasome-mediated gene expression in our in vitro AD model system. We have also observed that Mithramycin A (MTM), an HDAC2 inhibitor, significantly upregulated the synaptic plasticity gene expression and downregulated HDAC2 in SH-SY5Y cells overexpressing amyloid precursor protein (SH-APP cells). Therefore, the introduction of these agents targeting amyloid-beta (Aβ) production, NLRP3 mediated neuroinflammation and HDAC2 levels will have a translational significance in the prevention of neuroinflammation and associated neurodegeneration in AD patients.